Comparing between Combined Financial Ratios Based on Cash Flow and Accrual Figures with Financial Ratios Based on Accrual Figures to Foresee the Companies Bankruptcies - Mohsen Khoshtinat; Mohammad Taghi Ghesvari (مطالعات تجربی حسابداری مالی, 2005)
In the present article, the power of financial ratios based on cash flow statement will be investigated, to foresee the companies' bankruptcies. To accomplish this, two metric models of Multiple Auditing Analysis and Logistic Regression are used, and their predictive power for bankruptcy of present companies of Tehran Stock Exchange is evaluated. Both models were using statistics of two groups of Tehran Stock Exchange companies. Both groups are composed of 32 companies who are the subject of the Article 141 of Commerce Act. The model of this analysis is KC and Bartzak (1985), which includes 9 financial ratios of accrual ratios of cash to total assets, current assets to total assets, quick ratio, sales to current assets, net income to total assets, and total liabilities to equity. It also includes cash flow statement rations, consisting of operational cash flow, operational cash flow to current liabilities, and operational cash flow to total liabilities. The statistical result of analysis is the indication of validity of both models and selected financial ratios. The two models can well predict the financial crisis of the companies one year before occurring.